2020
DOI: 10.3390/diagnostics10090641
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Visual Perception and Microstructural Change of the Superior Longitudinal Fasciculus in Patients with Brain Injury in the Right Hemisphere: A Preliminary Diffusion Tensor Tractography Study

Abstract: Right hemisphere brain damage often results in visual-spatial deficits. Because various microstructural changes of the superior longitudinal fasciculus (SLF) after a stroke in the right hemisphere affect visual perception, including neglect, the present study investigates the relationship between both microstructural change and lateralization of SLF and visual perception, using diffusion tensor imaging (DTI) in patients with lesions in the right hemisphere. Eight patients with strokes (five patients with intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 43 publications
(78 reference statements)
1
9
0
1
Order By: Relevance
“…They observed a dramatically decreased activity, impaired responses to visual stimuli and spatial perception deficits of the primary visual cortical neurons [ 34 ]. Impaired visual perception is observed in approximately 75% of the patients with brain damage, and it frequently results in serious limitations concerning independent functioning [ 14 ]. These patients demonstrate visual field.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They observed a dramatically decreased activity, impaired responses to visual stimuli and spatial perception deficits of the primary visual cortical neurons [ 34 ]. Impaired visual perception is observed in approximately 75% of the patients with brain damage, and it frequently results in serious limitations concerning independent functioning [ 14 ]. These patients demonstrate visual field.…”
Section: Discussionmentioning
confidence: 99%
“…Observation of the patients allowed to discover that the subjects with initial problems with extreme saccadic movements (quick looking at the other side of the screen) were able to look in the direction they previously found difficult to see after completion of the oculomotor training course. In certain patients, difficulties with symmetric ocular movements result from, e.g., visual–spatial deficits (or neglect) [ 14 ]. The neglect is generally defined as inability to perceive, to report and to orient to sensory events towards one side of a space, contralaterally to the side of the lesion, with or without a primary sensory deficit [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SLF is involved in speech processing ( 31 , 32 ), musical processing ( 33 ), spatial attention ( 34 ) and memory ( 35 ), decision making ( 36 ), visual perception ( 37 ), and perceptual organisation ( 38 ). For example, right-hemisphere brain damage e.g., induced by stroke often results in visual-spatial deficits, such as a neglect ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…The SLF is involved in speech processing ( 31 , 32 ), musical processing ( 33 ), spatial attention ( 34 ) and memory ( 35 ), decision making ( 36 ), visual perception ( 37 ), and perceptual organisation ( 38 ). For example, right-hemisphere brain damage e.g., induced by stroke often results in visual-spatial deficits, such as a neglect ( 37 ). McKendrick et al ( 7 ) demonstrated that patients with visual snow demonstrated reduced centre-surround contrast suppression and elevated luminance increment thresholds in noise but did not differ on a global form or global motion task.…”
Section: Discussionmentioning
confidence: 99%